Transdermal hormone therapy of the menopausal period – state of the art in 2010 - Pertyński, Tomasz; Stachowiak, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2010)
In this article some up-to-date information on transdermal hormone therapy is presented. Lack of first-pass effect, therapeutic efficacy and safety make transdermal MHT a therapy of the first choice for many menopausal subjects.